2007
DOI: 10.2319/0003-3219(2007)077[0483:smooww]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Orthodontic Wires with Photocatalytic Titanium Oxide for its Antiadherent and Antibacterial Properties

Abstract: The surface modification of orthodontic wires with photocatalytic TiO(2) can be used to prevent the development of dental plaque during orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 23 publications
3
57
0
1
Order By: Relevance
“…However, the rutile form is more thermodynamically stable and resistant against fracture (Choi et al, 2007;Horiuchi et al, 2007; al., 2009). It is also commonly stated that anatase crystals have the highest photocatalytic activity among the crystal types of TiO 2 (Choi et al, 2007;Chun et al, 2007;Horiuchi et al, 2007;Choi et al, 2009;Özyildiz et al, 2010). Since traditional methods present problems with observing the crystal structure of the coated thin films, we used GIXRD and a separate glass slide, which was coated under the same conditions as the arch wires (Hamid, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rutile form is more thermodynamically stable and resistant against fracture (Choi et al, 2007;Horiuchi et al, 2007; al., 2009). It is also commonly stated that anatase crystals have the highest photocatalytic activity among the crystal types of TiO 2 (Choi et al, 2007;Chun et al, 2007;Horiuchi et al, 2007;Choi et al, 2009;Özyildiz et al, 2010). Since traditional methods present problems with observing the crystal structure of the coated thin films, we used GIXRD and a separate glass slide, which was coated under the same conditions as the arch wires (Hamid, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds exist that are capable of photocatalytic degradation of microorganisms, although TiO 2 has gained the most popularity amongst the other photocatalysts for its chemical stability as well as its property of not being hazardous to health (Chun et al, 2007;Akhavan, 2009). Although it has 3 crystal structures that can be produced by different oxidation procedures, the anatase form has the highest reactivity (Horiuchi et al, 2007;Akhavan, 2009;Choi et al, 2009;Sato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These methods have their greatest potential in thin organic films and coatings [82]. Chun et al [83] applied photocatalytic titanium oxide (TiO 2 ) to stainless steel orthodontic wires using this method to evaluate its antibacterial and antiadherent properties. The results of their investigation showed that photocatalytic TiO 2 may be used to prevent the development of dental plaque during orthodontic treatment.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…For this reason they have been investigated as potential antimicrobial coatings and inhibit bacterial growth when attached to glass, paper, plastic and metal [5][6][7][8] . For example, methacryloyloxydodecylpyridinium, was incorporated into dental resin composite and reduced microbial activity without leaching 9 .…”
Section: Introductionmentioning
confidence: 99%